Influence of no‐tillage versus tillage system on common vole (Microtus arvalis) population density. Issue 6 (16th February 2018) - Heroldová, Marta; Michalko, Radek; Suchomel, Josef; Zejda, Jan
Abstract: BACKGROUND: While the 'no‐tillage' management system generally improves soil properties and helps to control arthropod pests, it may also intensify crop infestation by the common vole ( Microtus arvalis Pallas). In this study, we evaluated the impact of soil management (no‐tillage or tillage), crop and previous crop (winter wheat or winter rape), and season (spring or autumn) on common vole density using data from the Common Vole Monitoring Programme undertaken by the Plant Protection Service of the Czech Republic between 2000 and 2009. RESULTS: Models predicted low mean values of vole infestation across management types, crops, and seasons. The untilled fields hosted significantly more voles than the tilled fields in spring but not in autumn. More common voles were found in winter rape than in winter wheat during both seasons. CONCLUSION: Recent studies suggest that no‐tillage management is more profitable than tillage management as a result of its positive impact on soil properties and pest control. During periods of high vole infestation, however, tillage may constitute an alternative strategy for reducing yield losses. © 2017 Society of Chemical Industry Abstract : Untilled fields hosted more voles but no‐tillage management is more profitable for a positive environmental effect.